Language Use in EFL Classroom Interaction: A Sociolinguistic Study - Agustine, Sherli; Asi, Natalina; Luardini, Maria Arina (Universitas Negeri Makassar, 2021)
Society and language cannot be separated, both have a relationship where society can be formed by the language they use. The diversity of languages used by teachers and students in EFL classroom interaction at MAN Katingan represents the existence of a bilingual or multilingual community. This research was conducted to describe how is the language use in EFL classroom interaction. The type of this research was descriptive research using the qualitative method. The subject were one of the English teachers and the students of the eleventh grade of MAN Katingan. The data collection was done by questionnaire using a google form to students and interview was done to the English teacher. The result showed the use of language at MAN Katingan in EFL classroom interaction was varied enough. Based on the studentsâ€™ view, teacher and students used 24,7% English, 40,4% Indonesian, 8,4% Banjarese, 0,9% Dayakese, and 26,2%Â mixed the language or used code-switching and code-mixing in EFL classroom interaction. On the other hand, the teacher stated that she mostly used code-switching and code-mixing. Sometimes, she used the local language to Â interact with the students in her EFL classroom.Keywords: language use: EFL: classroom interaction: sociolinguistics study